2007
DOI: 10.1002/jso.20937
|View full text |Cite
|
Sign up to set email alerts
|

The significances of lymph node micrometastasis and its correlation with E‐cadherin expression in pT1‐T3N0 gastric adenocarcinoma

Abstract: Lymph node MM in histologically node-negative gastric cancer was significantly correlated with poor 5-year survival rate. The determination of E-cadherin expression in primary gastric tumor may be useful in prediction of the MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
0
35
0
2
Order By: Relevance
“…5 Lymph node metastasis (LNM) is generally responsible for the high mortality rate of gastric cancer. 6 Especially in recent years, the importance of lymph node micrometastasis (LNMM) has been increasingly recognized, 7 which is regarded as the supplement of current staging systems for predicting prognosis or planning adjuvant therapy. 8 However, it remains difficult to diagnose lymphatic metastasis preoperatively or to supervise its recurrence postoperatively by imaging tests, 9 let alone to diagnose the micrometastasis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Lymph node metastasis (LNM) is generally responsible for the high mortality rate of gastric cancer. 6 Especially in recent years, the importance of lymph node micrometastasis (LNMM) has been increasingly recognized, 7 which is regarded as the supplement of current staging systems for predicting prognosis or planning adjuvant therapy. 8 However, it remains difficult to diagnose lymphatic metastasis preoperatively or to supervise its recurrence postoperatively by imaging tests, 9 let alone to diagnose the micrometastasis.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, a relationship between SIRT1 activity and expression of the tumor suppressor adhesion molecule, E-cadherin, 22 is closely related to the metastatic potential of tumors. 23 This has led to the hypothesis that SIRT1 may promote tumorgenesis and drug resistance and provide a potential target for cancer therapy. 24,25 It has also been shown that SIRT1 may inhibit proliferation and tumor formation.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of E-cadherin expression in the primary tumor, especially occurring in diffuse type gastric carcinoma [45], might be a possible explanation for this finding as it leads to decreased intercellular adhesion and correlates with tumor cell dissociation [46]. A higher probability for mi and ITC in diffuse histologic type was also reported by other authors [6,10,11,17,45] leading to the conclusion that LN immunohistostaining is of special importance for this cancer entity. Furthermore, positive correlation between LN mi and total gastrectomy was observed in this study, possibly because total gastrectomy led to a significantly higher number of dissected LN in comparison to patients, who received only partial gastric resection (88.5 % of patients with total gastrectomy had more than 15 LN removed versus 67.6 % of patients with distal gastric resection).…”
Section: Survival Analysismentioning
confidence: 57%
“…Immunohistochemistry is a frequently described method to detect ITC and mi not visible in routinely performed haematoxylin and eosin (HE) stain [6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Besides immunohistostaining serial sectioning and molecular methods are options to improve the accuracy of pathologic examination.…”
Section: Introductionmentioning
confidence: 99%